Acceptability and Nutritional Value of Mackerel Fish Nugget with Additions of Moringa Leaves Flour for Stunting Children Under-Five Years in West Nias Regency - Diah Sekar Haruni; Adi Magna Patriadi Nuhriawangsa; Ratih Puspita Febrinasari (Nusantara Science and Technology Proceedings, 2024)
Stunting is one of a nutritional problems. Mackerel contains high protein which is important for growth. Moringa leaves contain high calcium and iron to overcome stunting. However, these two ingredients are very low in utilization as food ingredients so food diversification is carried out by making nuggets that are popular with children. The goal of this study was to determine the acceptability and nutritional value of mackerel nuggets with the addition of moringa leaf flour for stunting children in West Nias Regency. This type of research was experimental with organoleptic and proximate test. The treatment is moringa flour addition of 3%, 5%, 7%. Data were analyzed with One Way ANOVA followed by Duncan's and using Kruskal Wallis followed by the Mann-Whitney test if the data did not meet one of the conditions for the Anova test. The hedonic test results showed that there was a significant difference in aroma (p=0.033), taste (p=0.001), and texture (p=0.043) but no effect on color (p=0.639). The nutritional value test results showed that there was an effect of moringa leaf addition on the moisture content (p=0.016), ash (p=0.001), protein (p=0.001), fat (p=0.001), carbohydrate (p=0.024), calcium (p=0.001), and iron (p=0.001) of mackerel nuggets. Moringa flour addition influenced the liking of aroma, taste, and texture but had no effect on aroma and was well received by children's panelists in the category of “like” with F1 with the highest acceptance. Moringa flour addition influenced the protein, calcium, and iron levels with the highest levels in F3.